INDIKATOR TASMI AL-QUR’AN DALAM MENINGKATKAN KUALITAS HAFALAN SANTRI DI PONDOK PESANTREN AL-HIKMAH PUTRA CIREBON - Subhanal Hanafi; Mohamad Joko Susilo (As-Sulthan Journal of Education, 2025)
This study aims to explore the main indicators in the application of the Tasmi' method that contributes to improving the quality of Al-Qur'an memorization of students at the Al-Hikmah Putra Islamic Boarding School in Cirebon. The activity of memorizing the Al-Qur'an is a great worship, which requires a systematic approach and appropriate strategies to maintain strong and consistent memorization. In practice, the Tasmi' method is not only used as a memorization evaluation tool, but also as a means of coaching that covers intellectual, emotional, and skills aspects. This study adopted a qualitative approach with a normative juridical method and analyzed data using the interactive model of Miles and Huberman through data collection techniques such as observation, interviews, and documentation. The study findings indicate six crucial indicators in the success of the Tasmi' method, namely: (1) simultaneous memorization of five juz as an indicator of memorization strength, (2) gradual and systematic implementation of the One Juz Exam (USJ), (3) flexible muraja'ah system without quantitative limitations, (4) active involvement of mentors in monitoring and evaluation, (5) synergy between internal and external motivation of students, and (6) increasing memory through intensive Tasmi' practice. The halaqah-based learning system also strengthens the educational relationship between teachers and students, creating an interactive and spiritual learning atmosphere. Overall, the Tasmi' method has proven effective not only in producing strong and mutqin memorization, but also in forming the character of students who have Qur'anic morals, are independent, and are able to practice the values of the Qur'an in everyday life. Therefore, this method is a comprehensive, sustainable, and relevant approach to memorization development for today's Islamic boarding school education needs.